2018
DOI: 10.1080/13803395.2018.1513453
|View full text |Cite
|
Sign up to set email alerts
|

False memories in patients with mild cognitive impairment and mild Alzheimer’s disease dementia: Can cognitive strategies help?

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that presents predominantly with impairments in learning and memory. Patients with AD are also susceptible to false memories, a clinically relevant memory distortion where a patient remembers an incorrect memory that they believe to be true. The use of cognitive strategies to improve memory performance among patients with AD by reducing false memories has taken on added importance given the lack of disease-modifying agents for AD. However, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 95 publications
(161 reference statements)
0
17
0
Order By: Relevance
“…Non-pharmacological techniques such as pill boxes and reminder notes can enable individuals with moderate or even severe amnesia due to stroke or encephalitis to live independently (Acevedo & Loewenstein, 2007). These memorial aids typically fail in patients with Alzheimer's disease (AD) due, in part, to an increased tendency to form false memories (Malone et al, 2018). False memories may occur in several forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacological techniques such as pill boxes and reminder notes can enable individuals with moderate or even severe amnesia due to stroke or encephalitis to live independently (Acevedo & Loewenstein, 2007). These memorial aids typically fail in patients with Alzheimer's disease (AD) due, in part, to an increased tendency to form false memories (Malone et al, 2018). False memories may occur in several forms.…”
Section: Introductionmentioning
confidence: 99%
“…False memories may occur in several forms. For example false memories may be related to events that never occurred or to events that are distorted or mis-remembered (Malone et al, 2018). It is possible that false memories have an equal or greater impact on function in the lives of patients with mild cognitive impairment (MCI) and AD dementia compared to forgetting itself.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the severity of cognitive impairment, or the outcome of a cognitive intervention, is a priority when developing patient-oriented strategies for functional amelioration [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) has been described as a progressive neurodegenerative disorder where learning and memory performance has been reduced, as well as rapid forgetting of new information (Malone et al, 2018). As well as memory loss, patients with AD also have a higher rate of memory distortions and false memories, in which patients remember an incorrect memory that is believed to be true.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, false memories have traditionally been viewed as negative, particularly in aging adults (e.g., Devitt & Schacter, 2016;Malone et al, 2018). However, recent research has demonstrated that the production of false memories need not always have negative implications (Akhtar et al, in press;Howe, 2011;Howe et al, 2011;Howe, Garner, Dewhurst, & Ball, 2010;Howe, Threadgold, Wilkinson, Garner, & Ball, 2017).…”
Section: Introductionmentioning
confidence: 99%